The Influence of Parenting Style on Student Academic Achievement Based on Gender - Angelina Sirait, Chrysti; Slameto (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The literature recognizes the importance of parenting and its impact on children's academic achievement at school. Many factors influence children's academic achievement, and parenting patterns and gender are significant factors that influence children's academic achievement outcomes at school. However, few studies still discuss the relationship between parenting and children's educational achievement outcomes based on gender. This study used a systematic literature review method. This study used three databases (Google Scholar, JSTOR, and Springer Link). The results of this study show that, based on authoritative, authoritarian, permissive, and neglectful parenting, authoritative parenting is the most effective parenting method in improving children's academic achievement, both girls and boys. In addition, with authoritative parenting, children can have good social and emotional skills.